The trend of sharenting among Malaysian parents: A preliminary study of intention and motivation - Li Hua Heng; Crendy Yen Teng Tan; Saroja Dhanapal (International Journal of Public Health Science (IJPHS), 2022)
Social media platforms and applications are increasing exponentially and has become a part of life for everyone. It is widely used by people to connect with large numbers of people without investing much time and effort. This led to the emergence of a new term, ‘sharenting’ which refers to parents sharing their children’s information on social media. The trend of sharenting is very predominant and has raised a lot of concerns in the western countries, but in Malaysia there is still a lack of adequate knowledge on this trend. Past research on this topic mainly focuses on the usage frequency, content and consequences of sharenting in Western countries. However, there is a dearth of literature on the intention and motivation of Malaysian parents’ inclination to this trend. In view of this, the current study employed a qualitative approach in exploring Malaysian parents’ intention and motivation of sharing children’s information on social media through the framework of Bandura’s social learning theory. The study targeted parents in Malaysia aged between 20 to 40 who often share their children’s information on social media. The research was conducted through one-to-one interviews and the findings from the interviews were analyzed using a thematic approach. This research is significant as it provides knowledge on the trend of sharenting of Malaysian parents. The paper ends with recommendation for further future research.